Macrophage Exosomes Induce Placental Inflammatory Cytokines: A Novel Mode of Maternal–Placental Messaging. (February 2016) - Holder, Beth; Jones, Tessa; Sancho Shimizu, Vanessa; Rice, Thomas F.; Donaldson, Beverly; Bouqueau, Marielle; Forbes, Karen; Kampmann, Beate
Abstract : Exosome trafficking from the placenta into the maternal circulation is well documented; the possibility that this trafficking is bi‐directional was unknown. We demonstrated clathrin‐mediated endocytosis of macrophage exosomes by the human placenta. We also demonstrated that macrophage exosomes induced placental production of cytokines interleukin (IL)‐6, IL‐8 and IL‐10. Exosomes therefore comprise an additional mechanism of immune cell signalling to the placenta, potentially facilitating protective responses to maternal inflammation and infection in pregnancy. This represents a novel mode of maternal–placental messaging.